Modifikasi Algoritma Caesar Chiper Dengan Menambahkan Key Untuk Peningkatan Keamanan - Rudolf Sinaga; Frangk (LPPM Universitas Potensi Utama, 2023)
This article discusses the modification of the Caesar Cipher algorithm by adding a key as a way to increase its security. Caesar Cipher is one of the classic algorithms used to encrypt messages by shifting each letter in the original message 3 times, where the shift is 3 times as the key used. However, even though Caesar Cipher is relatively simple and easy to implement, this algorithm is vulnerable to brute force attacks because it only has 26 possible shift ciphers. Therefore, the authors propose a modification by adding a key to this algorithm. In this modification, keys are added to each letter of the original message before it is shifted, thus making the resulting shift patterns more complex and difficult to solve. The test results show that modifying the Caesar Cipher algorithm with the addition of a key can improve message security. However, the author also realizes that although the addition of keys can improve security, this algorithm still has other weaknesses such as being vulnerable to frequency analysis attacks. Therefore, the authors conclude that this modification can only improve Caesar Cipher's security to a certain level and still needs to be combined with other encryption techniques to achieve better security.